2016
DOI: 10.3390/f7030071
|View full text |Cite
|
Sign up to set email alerts
|

The Urban Environment Can Modify Drought Stress of Small-Leaved Lime (Tilia cordata Mill.) and Black Locust (Robinia pseudoacacia L.)

Abstract: Abstract:The urban environment characterized by various stresses poses challenges to trees. In particular, water deficits and high temperatures can cause immense drought stress to urban trees, resulting in reduced growth and die-off. Drought-tolerant species are expected to be resilient to these conditions and are therefore advantageous over other, more susceptible species. However, the drought tolerance of urban trees in relation to the specific growth conditions in urban areas remains poorly researched. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 61 publications
3
33
1
Order By: Relevance
“…In this study, we found that drought had a relatively small impact on fine root growth of T. cordata and it invested less energy than T. tomentosa on belowground growth, the fine root biomass only slightly varied between control and drought treatment trees. Moser et al [21] found that T. cordata showed a continued decrease in aboveground growth after a drought event while our results showed the congruent growth for belowground processes. This implies that the belowground part did not actively react to cope with drought stress.…”
Section: Total Fine Root Biomasssupporting
confidence: 54%
“…In this study, we found that drought had a relatively small impact on fine root growth of T. cordata and it invested less energy than T. tomentosa on belowground growth, the fine root biomass only slightly varied between control and drought treatment trees. Moser et al [21] found that T. cordata showed a continued decrease in aboveground growth after a drought event while our results showed the congruent growth for belowground processes. This implies that the belowground part did not actively react to cope with drought stress.…”
Section: Total Fine Root Biomasssupporting
confidence: 54%
“…This approach might be improved by introducing a dependency on climate and soil type, particularly by encompassing drought stress events [61] and other stress factors that might depend on the degree of air pollution or salt application. Pretzsch et al (2017) [62] showed that the urban trees in Europe have accelerated their growth since 1960 because of the effects of climate change, with considerable differences in different climate regions.…”
Section: Uncertainties Associated With Parameterizationmentioning
confidence: 99%
“…This tree was considered as a suitable candidate for phytoremediation owing to its developed root system, high biomass productivity, environmental stress tolerance and ability of atmospheric nitrogen fixation [24][25][26].…”
Section: Introductionmentioning
confidence: 99%